Changes of cortical epileptic afterdischarges under the influence of convulsant drugs - Koryntová, H; Kubová, H; Tutka, P; Mares, P (Brain research bulletin, 2002)
Convulsant drugs picrotoxin (0.5 and/or 1 mg/kg, intraperitoneal (i.p.)) and pentylenetetrazol (10 and/or 20 mg/kg, i.p.) were used to compromise GABAergic inhibition, caffeine (75 and/or 150 mg/kg, i.p.) to antagonize adenosinergic system to study the role of inhibition in cortical epileptic afterdischarges. Rats with implanted cortical stimulation and registration electrodes were stimulated four times at 10-min intervals, drugs were injected between the first and second stimulation. Four different phenomena were evaluated: movements directly bound to stimulation were intensified by all three drugs, i.e., excitability of the cerebral cortex was increased. Incidence of two types of afterdischarges (spike-and-wave rhythm and "limbic" type) was not changed by any drug, i.e., the transition of epileptic activity into limbic structures was not increased. Afterdischarges were most efficiently prolonged by caffeine, i.e., caffeine probably interferes with mechanism(s) arresting cortical afterdischarges. The intensity of clonic seizures accompanying spike-and-wave afterdischarges, i.e., spread of epileptic activity into the motor system was only transiently increased by picrotoxin, the effects of caffeine did not reach the level of statistical significance. Our results indicate various mechanisms and diverse role of the two inhibitory systems in generation of evaluated phenomena.
Keywords: Pentylenetetrazole; Epilepsy, Tonic-Clonic; Rats; Electroencephalography; inhibitory fosfodiesteras; epilepsie tonicko-klonická; konvulziva; Rats, Wistar; kofein; mužské pohlaví; elektroencefalografie; Phosphodiesterase Inhibitors; Caffeine; krysa rodu Rattus; pikrotoxin; mozková kůra; zvířata; Cerebral Cortex; elektrická stimulace; potkani Wistar; pentylentetrazol; Convulsants; Electric Stimulation; Picrotoxin; Male; Animals